Application of Circulating Tumor DNA in Biosensors - Zhang Yifan (MATEC Web of Conferences)
As a marker of tumor detection, circulating tumor DNA (ctDNA) is of great significance for the early screening, diagnosis, and treatment of cancer. However, the current detection methods still have problems such as insufficient sensitivity and specificity, and low abundance leads to inaccurate detection results. Biosensors have great potential in ctDNA detection, so the combination of biosensors and ctDNA is the main research direction in this paper. After the ctDNA is released, it is combined with a suitable bioreceptor and detected by two common biosensors: electrochemical sensors and optical sensors. The detected numerical changes or phenomena can provide considerable convenience for patients, and the advantages of ctDNA can be used to achieve a low-cost, time-consuming, convenient, and portable monitoring system. Research has shown that this sensor has played a significant role in early tumor screening and disease monitoring, providing a powerful tool for accurate diagnosis of cancer. In the future, sensor performance will be further optimized based on this foundation to promote the development of clinical applications.